Pengembangan Alat Evaluasi Pembelajaran Matematika Berbasis Two Tier Multiple Choice Menggunakan Ispring Suite 9 - Rovita, Chusnul Amalia; Zawawi, Irwani; Huda, Syaiful (Postulat : Jurnal Inovasi Pendidikan Matematika, 2020)
In the era of the industrial revolution 4.0 and the pandemic era, innovation is needed in the development of technology-based evaluation tools. One of them is the ispring suite 9. Evaluation tool is important because it can help the process of evaluating educators to find out information on the achievement of results during the learning process. In addition to learning outcomes, evaluation can also determine the ability of students to understand concepts. One of them is a two tier multiple choice evaluation test. Two tier multiple choice is a form of two-tier multiple choice evaluation test. The purpose of this study is to develop a learning evaluation tool that can find out students' understanding of concepts and can be used online. The research and development model used is 4D. The research instruments used were interview sheets, validation sheets, test instruments, and questionnaires. Data analysis techniques used qualitative and quantitative. The result of this study is a two-tier multiple choice based mathematics evaluation tool using ispring suite 9 which is seen from: (1) the percentage of validation results from media experts is 90.5% and material experts is 96.5%, both of which fall into the very feasible category. (2) the quality of the items seen from the validity obtained 8 valid items with a reliability of 0.815. Judging from the level of difficulty, the percentage is 10% difficult, 80% moderate and 10% easy, the distinguishing power is obtained 5 questions are included in the good category, 3 questions are quite good, 1 question is very good, and 1 question is bad, and the effectiveness of the distractor has 9 distractors who selected > 5% of all students. (3) The percentage of students 'conceptual understanding after evaluating two tier multiple choices is 50.5%, which is in the sufficient category, and the results of the students' responses are 82% which is included in the very interesting category.